PERAN KEPALA MADRASAH DALAM MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA DI MADRASAH IBTIDAIYAH - Wahyudi, Imam; Nurul Aulia Sari; Qodriyana Kusumastiti; Syifa Zakia Rahma Azizah; Siti Zulaikha (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
The curriculum serves as a fundamental foundation in the development of education in Indonesia. Currently, the curriculum in Indonesia is transitioning from the 2013 Curriculum to the Merdeka Curriculum. This transition process requires the strategic role of the Head of Madrasah in supporting its implementation, namely as an Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator. Without these roles, the implementation of the Merdeka Curriculum in Madrasah Ibtidaiyah cannot proceed as expected, especially since Madrasah Ibtidaiyah has distinctive Islamic characteristics. This study employs a qualitative method with a case study approach conducted at Madrasah Ibtidaiyah Legowetan. Data collection techniques include interviews with the Head of Madrasah Ibtidaiyah Legowetan, observation, and documentation. Data analysis is carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the role of the Head of Madrasah Ibtidaiyah Legowetan has been actively carried out in accordance with its functions. Although various challenges were encountered in its implementation, these challenges did not become obstacles but rather served as drivers for the successful implementation of the Merdeka Curriculum at Madrasah Ibtidaiyah Legowetan.